Perbandingan antara Visus Hasil Pemeriksaan Refraksi pada Tingkat Pencahayaan Optimal, Rendah, dan Tinggi di Ruang Laboratorium Refraksi Optisi STIKes Dharma Husada Bandung - Suparni Suparni; Benita Erma Indriyani (Sehat MasadaJurnal, 2020)
Visual acuity are influenced by several factors such as age, lighting, glare, pupil size, working period, and duration of work. The purpose of the research was to determine the differences in the results of refraction test at each level of lighting in the refraction optic laboratory room of STIKes Bandung Dharma Husada in 2019. The research’s design was descriptive, with measurements visual acuity and visual correction at optimal (300 lux), low (150 lux), and high (750 lux) lighting levels. The sample of this research used accidental sampling technique, first and second grade regular students of Diploma III Refractionist Optician of STIKes Dharma Husada Bandung, amounting to 35 people. Data processing is done automatically, then analyzed univariately to see the distribution of the variables research. The result found a comparison of visual acuity differences at optimal, low and high lighting levels is as much as 27%. Comparison of differences in visual correction at optimal, low and high lighting levels is 25%. The writer recommends lighting in the laboratory to be renewed because the existing lighting is far from the standard for conducting refraction test.